Turismo cultural e religioso - desenvolvimento de itinerários experienciais em terras de Tarouca - Teixeira, Helena (2017)
This paper focuses on the religious and cultural heritage of the Douro-South region. The region was studied identifying the specificities of the historical centres and their surroundings. We examined the region's vocation to root and develop tourism activities linked to cultural and religious phenomenon. Moreover, we intended to determine whether the development of tourist and religious itineraries, would be feasible and desirable with the aim of developing tourism. Using data collected in surveys, aspects of performance and satisfaction with the destination are studied. Thus, it was possible to infer the relationship between those who manage the heritage and the territory and their visitors and determine the main deficiencies pointed out by the visitors, taking into account some problems related to managing, and interpreting monuments and tourist information. Finally we create a sightseeing tour which highlights the history, traditions and heritage of the region, with particular focus on St. Bernard’s message.